Sulfotyrosine-Mediated Recognition of Human Thrombin by a Tsetse Fly Anticoagulant Mimics Physiological Substrates. Issue 1 (21st January 2021) - Calisto, Bárbara M.; Ripoll-Rozada, Jorge; Dowman, Luke J.; Franck, Charlotte; Agten, Stijn M.; Parker, Benjamin L.; Veloso, Rita Carvalho; Vale, Nuno; Gomes, Paula; de Sanctis, Daniele; Payne, Richard J.; Pereira, Pedro José Barbosa
Summary: Despite possessing only 32 residues, the tsetse thrombin inhibitor (TTI) is among the most potent anticoagulants described, with sub-picomolar inhibitory activity against thrombin. Unexpectedly, TTI isolated from the fly is 2000-fold more active and 180 Da heavier than synthetic and recombinant variants. We predicted the presence of a tyrosine O -sulfate post-translational modification of TTI, prompting us to investigate the effect of the modification on anticoagulant activity. A combination of chemical synthesis and functional assays was used to reveal that sulfation significantly improved the inhibitory activity of TTI against thrombin. Using X-ray crystallography, we show that the N-terminal sulfated segment of TTI binds the basic exosite II of thrombin, establishing interactions similar to those of physiologic substrates, while the C-terminal segment abolishes the catalytic activity of thrombin. This non-canonical mode of inhibition, coupled with its potency and small size, makes TTI an attractive scaffold for the design of novel antithrombotics. Graphical Abstract: Highlights: The diminutive TTI is one of the most potent anticoagulants reported to date Post-translational tyrosine O -sulfation enhances TTI activity over 1000-fold TTI is a bivalent inhibitor that targets thrombin's exosite II and active site The binding mode of TTI resembles that of physiologic thrombin substrates Abstract : Calisto et al. discovered that post-translational O -sulfation of two tyrosine residues of the tsetse thrombin inhibitor—one of the smallest and most potent natural anticoagulants known—increases its affinity for thrombin by more than 1000-fold and showed that the inhibitor mimics the binding of natural substrates of thrombin.